Adobe's Acrobat -- the Electronic Journal Catalyst? - Brailsford, David F. (University of Manitoba, 1993)
Adobe's Acrobat software, released in June 1993, is based around a new Portable Document Format (PDF) which offers the possibility of being able to view and exchange electronic documents, independent of the originating software, across a wide variety of supported hardware platforms (PC, Macintosh, Sun UNIX etc.).